Extent of Freedom of Religion in a Transforming India - Avnish Singh; Preeti Singh (AG Volumes, 2026)
Religion is an indispensable part of human existence. Freedom of religion is considered as the third most important civil liberty after the right to life and personal liberty and the freedom of speech and expression. The Indian Constitution guarantees freedom of religion and acknowledges the individual’s autonomy in his or her relationship with God. However, the Supreme Court of India, through the creation and continued use of the essentiality test, has tried to reform religion by restricting the scope of this freedom. Court has resorted to the essential and non-essential religious practice test to determine the essential aspects of this right. The Court has applied this test in an inconsistent manner, repeatedly changing the method of determining essentiality, seriously undermining religious liberty. This chapter examines constitutional framework pertaining to the various aspects of this right. It further discusses the various judicial pronouncements and recent developments to demonstrate the impact of the essentiality test on religious freedom